Empowerment and its Relation with the Job Performance Among the Bank Employees in the Kingdom of Bahrain - Neda Abdulkarim Albaqqali; Jayendira Sankar (International Journal of Engineering and Management Research, 2019)
Empowerment of employees give them the power and responsibility in order to enhance their self-confidence and give them freedom to perform well. The performance of employees is the final product sought by all organizations, which is an indicator for success and failure. The primary objective of this study is to assess the extents of empowerment and the level of job performance among the bank employees in the Kingdom of Bahrain and if there is a significant correlation between both variables. The descriptive study was based on surveying 250 employees and managers from 5 main banks in Bahrain. The questionnaire measured the empowerment level as well as the job performance level among the respondents and the correlation between them. As considered the main two variables of the study. The survey questionnaire was developed and modified by the researcher according to the scope of the study. The response rate was 80%. The study data and hypotheses were examined by statistical analysis done on SPSS 25.0. Most of the respondents found that the level of empowerment and job performance were at very high level in banks in Bahrain. The study found a strong correlation between empowerment of employees and job performance. Thus, the alternative hypothesis was accepted. The findings support the high level of empowerment of employees and job performance and there is a strong correlation between them.